Obtenção e caracterização de biocompósitos formulados com fécula da casca e da entrecasca de mandioca (Manihot esculenta Crantz) e galactomananas de alfarroba (Ceratonia siliqua L.) e reforçados com nanofibras de material lignocelulósico. - Pãmella Fronza Câmara (2022)
The call for a more sustainable world scenario has grown in recent years, due to the environmental impacts caused by the inadequate disposal of plastic packaging and agro-industrial waste. In order to provide sustainable materials, the first practical application of this thesis aimed to extract starch from the bark and cassava peel as an alternative to generate a by-product with higher added value. The starch was extracted and characterized in relation to physical, chemical, rheological, structural, thermal and morphological properties. A fine, white powder was obtained, with a total starch content of 23.2%. The complete gelatinization of this by-product occurs at temperatures above 65 ºC, forming a pseudoplastic gel. The high thermal stability of the extracted starch suggests strong intermolecular and intramolecular interactions of the molecules. In FTIR spectra, the presence of cellulose in the extracted product can be observed. Micrographs indicated a predominance of polygonal, truncated and oval shapes, characteristic of starch granules. The extracted starch was used in the development of biocomposites incorporated from carob galactomanans. Five formulations were prepared by casting method and characterized. Structural analysis showed similar patterns for the samples evaluated. The results of the TGA and DSC analyses showed good thermal stability and the possibility of application of the materials under refrigeration conditions. Carob galactomanans interacted positively with the other matrix constituents promoting improvements in barrier and mechanical properties of biocomposites. Finally, the last practical application aimed to isolate cellulose nanofibers from the residual pie from the extraction of the starch, and incorporate them into the formulation of bionanocomposites, aiming at the full use of these residues. To this end, we used the formulation that presented the best performance in the previous stage (A4-75F/25G). Nanofibers composed predominantly of cellulose were efficiently isolated by chemical pretreatment, enzymatic hydrolysis and mechanical treatment. In the FTIR and TGA spectra, the predominance of thermally stable cellulose was confirmed. Micrographs obtained by AFM revealed that the nanofibers produced presented an average diameter of 5 nanometers. From this characterization, the isolated nanofibers were used in the formulation of bionanocomposites. Three distinct concentrations were studied (0.5%, 1.5% and 2.5%). When analyzing the FTIR spectra, structural similarities were observed. The peaks of NMR 13C confirmed the similarity between the compounds and also the structural preservation of starch, galactomanans and cellulose. The increase in the concentration of nanofibers provided an increase in the temperature of thermal degradation of bionanocomposites, in which a new thermal event was observed in the formulation that had the addition of 2.5% of nanofibers. The addition and increase in the concentration of nanofibers reduced the solubility of bionanocomposites from 70.35% (Control Formulation) to 15.14% (Formulation plus 2.5% of nanofibers). The increase in the concentration of nanofibers also provided improvements in water vapor permeability. All bionanocomposites were stable at different pH ranges and were considered biodegradable within 7 days. In general, bionanocomposite with 1.5% nanofibers showed the best performance. Therefore, it is concluded that the use of these residues will contribute to reduce the environmental impacts caused by the disposal of synthetic packaging and agro-industrial waste.